Experimental infections with Zika virus strains reveal high vector competence of Aedes albopictus and Aedes aegypti populations from Gabon (Central Africa) for the African virus lineage - Davy Jiolle; Isabelle Moltini-Conclois; Judicaël Obame-Nkoghe; Patrick Yangari; Angélique Porciani; Bethsabée Scheid; Pierre Kengne; Diego Ayala; Anna-Bella Failloux; Christophe Paupy (Emerging Microbes and Infections)
The two main Zika virus (ZIKV) vectors, Aedes albopictus and Aedes aegypti (invasive and native species, respectively), are present in Gabon (Central Africa). The aim of this study was to determine the entomological ZIKV risk associated with these mosquito species in Gabon by evaluating their vector competence for an African (i.e. representative of the endemic strains circulating in sub-Saharan Africa) and two Asian (i.e. representatives of exogenous epidemic strains that could be introduced) ZIKV strains. The transmission efficiency of one Ae. aegypti and two Ae. albopictus field-collected populations from Libreville and Franceville was assayed at day 7, 14 and 21 after experimental oral infection. The two mosquito species could transmit all three ZIKV strains already at day 7 post-infection, but transmission efficiency was higher for the African strain than the non-African strains (>60% versus <14%; incubation period of 14–21 days). The two mosquito species exhibited comparable vector competence for ZIKV, although the amount of viral particles (African strain) in saliva was significantly higher in Ae. albopictus than Ae. aegypti at day 14 post-infection. These findings suggest that overall, ZIKV risk in Gabon is mainly related to virus strains that circulate endemically across sub-Saharan Africa, although the transmission of non-African strains remain possible in case of introduction. Due to its high infestation indexes and ecological/geographical ranges, this risk appears mainly associated with Ae. albopictus. Vector surveillance and control methods against this invasive mosquito must be strengthened in the region to limit the risk of future outbreaks.